The adoption of banking technology and electronic financial services: evidence from selected bank customers in Ethiopia. (5th December 2019) - Jerene, Wondwossen; Sharma, Dhiraj
This study was aimed to investigate factors that determine bank customers' intention to adopt electronic banking technologies and electronic financial services in Ethiopia. The TAM model was used that constructed with perceived financial trust, perceived financial risk, subjective norm, and awareness as exogenous factors that predict bank customers' intention to adopt digital technologies. Self-administered questionnaire was used for data collected from 412 bank customers and the exploratory factor analysis (EFA) of data confirmed it was internally consistent enough to measure each factor. Similarly, the confirmatory factor analysis (CFA) of data was revealed that there was no concern of convergent and discriminant validity. According to SEM analysis using AMOS, the finding of the study shows perceived ease of use, perceived usefulness, perceived financial trust, subjective norm and awareness about new electronic banking technology positively predict bank customers' intention to adopt it. However, perceived financial risk negatively influences customers' intention to adopt banking technology and researchers' suggestions were forwarded in the paper.